Efficient removal of both basic and non-basic nitrogen compounds from fuels by deep eutectic solvents. Issue 1 (24th September 2015) - Ali, Mohammad Chand; Yang, Qiwei; Fine, Andrew Aaron; Jin, Wenbin; Zhang, Zhiguo; Xing, Huabin; Ren, Qilong
Abstract : Both basic and non-basic nitrogen compounds can be efficiently removed from fuels by deep eutectic solvents. Abstract : The removal of nitrogen compounds (N-compounds) from fuels has attracted considerable attention because of the necessity to reduce nitrogen oxide emission and improve sulfur elimination. In this work, we reported a novel denitrogenation method of fuels using deep eutectic solvents (DESs) as extractants, and demonstrated the essential role of a rational control of the physicochemical character of DESs in achieving superior denitrogenation performance. Among the investigated DESs, the 1 : 2 molar mixture of choline chloride and phenylacetic acid presented the best denitrogenation performance, showing simultaneous efficient removal of both basic and non-basic N-compounds. Without chemical reactions, the extraction efficiencies of pyridine and carbazole at 308 K with a 1 : 1 DES : oil mass ratio were 99.2% and 98.2%, respectively, and the selectivities to n -heptane were higher than 10 000. This was better than the performance of compared conventional solvents. The extraction efficiency was not sensitive to the DES : oil mass ratio and temperature, and remained unchanged after four regeneration cycles. In addition to the "green solvents" character of DESs, these results collectively demonstrate the considerable potential of DESs as promising materials for the green and efficient denitrogenation of fuels.